A "glass-ceiling" effect for immigrants in the Italian labour market? - Carlo Dell'Aringa; Claudio Lucifora; Laura Pagani (Institute for the Study of Labor (IZA), 2012)
This paper investigates earnings differentials between immigrants and natives. We focus on returns and on the (imperfect) international transferability of human capital. Data are drawn from the 2009 Italian Labour Force Survey (LFS). We show that returns to human capital are considerably lower for immigrants as compared to natives and that there is no return to pre-immigration work experience, suggesting imperfect transferability of human capital. We also explored the role of human capital, for immigrants and natives, in explaining inter-occupational and intra-occupational earnings progression (differentials). Our findings suggest that the returns on human capital (main source of wage progression) for immigrants (is) are mainly driven by intra-occupational earnings progression. Moreover, and contrary to what is observed for natives, we detect through quantile analysis a glass-ceiling effect for immigrant workers, who appear to face a large penalty in accessing high paying occupations. A number of robustness checks confirm our main results.
urn:nbn:de:101:1-201301212214
Keywords: J31; J24; J61; F22; 330; migration; earnings; human capital portability; occupational attainment; Lohndifferenzierung; Migranten; Bevölkerung; Humankapital; Bildungsertrag; Erwerbsverlauf; Italien